Determinants of Poverty in Nigeria: A Time Series Analysis - Takon Samuel Manyo (International Journal of Business and Quality Research, 2025)
The study investigated the determinants of poverty in Nigeria using annual time series data for twenty-three years (2000-2022). The study strives to specifically evaluate the impact of corruption, unemployment, economic instability, and population growth rate on poverty in Nigeria. Secondary data collated from the CBN statistical bulletin and the World Bank indicator for the period was used for the study. Employing the ordinary least squares (OLS) regression technique and ex-post facto research design for the statistical computations. The findings of the correlation test carried out, discovered that all the selected determinants (corruption, unemployment, economic instability and population growth) have a significant positive and negative correlation on poverty levels in Nigeria. The OLS regression model employed in this study shows that the regression model concludes that corruption, unemployment rate and population growth rate are positively associated with poverty level, while and economic instability is negatively associated with poverty level but was found to be statistically insignificant. Based on the finding of the study, it was concluded that efforts should be made to reduce corruption and manage population growth rates to curb poverty levels. This could be achieved through implementing strict anti-corruption measures and promoting good governance practices.